2014 IEEE Radar Conference 2014
DOI: 10.1109/radar.2014.6875741
|View full text |Cite
|
Sign up to set email alerts
|

Range limited adaptive pulse compression via linear Bayes estimation

Abstract: The original adaptive pulse compression (APC) algorithm and its modified version, the Gain-Constraint APC (GCAPC), have the processing window decreasing effect, i.e. the length of the estimating output will decrease by a constant on each iteration stage. As a result, the iteration number is limited by the available input length and the extra computational load is inevitable for large initial processing window. Our analysis indicates that the estimating methods in APC and the GCAPC algorithms are special cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Consequently, we conclude that FAMPC and MAMPC can significantly reduce the computational complexity in comparison with full-dimension AMPC algorithm. Output: An estimation matrixX; 1: Initialize q = 0, m = 0, l = 0 and range-Doppler plane X (0) using traditional matched filter method; 2: Construct matrix G and F by (6) and (7); 3: …”
Section: The Joint Procedures Of Mampc Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, we conclude that FAMPC and MAMPC can significantly reduce the computational complexity in comparison with full-dimension AMPC algorithm. Output: An estimation matrixX; 1: Initialize q = 0, m = 0, l = 0 and range-Doppler plane X (0) using traditional matched filter method; 2: Construct matrix G and F by (6) and (7); 3: …”
Section: The Joint Procedures Of Mampc Algorithmmentioning
confidence: 99%
“…In [5], the adaptive pulse compression (APC) was proposed, which was shown to successfully suppress the range sidelobes over a variety of *Correspondence: cuiguolong@uestc.edu.cn 1 University of Electronic Science and Technology of China, 2006 Xi Yuan Ave, West Hi-tech Zone, Chengdu, China Full list of author information is available at the end of the article stressing scenarios. Li et al [6] has demonstrated that gain-constraint-APC (GCAPC) [7] has better estimating performance especially for weak targets compared to original APC algorithm [5].…”
Section: Introductionmentioning
confidence: 99%
“…According to [8], the GCAPC algorithm has consistent advantage to the APC in terms to estimation performance of targets with small reflection coefficients. Therefore we implement the MAMPC by applying the GCAPC to process the received signal in range and Doppler dimensions sequentially.…”
Section: The Mampc Algorithmmentioning
confidence: 99%
“…The MAMPC algorithm processes the two-dimension MMSE cost function by implementing in the range dimension and the Doppler dimension sequentially. In addition, [8] has demonstrated that gain-constraint-APC (GCAPC) [9] has better estimating performance especially for small targets compared to original APC algorithm [10]. Therefore, we implement MAMPC in basic estimating stages by applying the GCAPC instead of the adaptive pulse compression (APC) to alleviate the signal to noise loss.…”
Section: Introductionmentioning
confidence: 99%